Assessing chemical control of earthworms at airports - Thomas W. Seamans; Bradley F. Blackwell; Glen E. Bernhardt; Daniel A. Potter (Wildlife Society Bulletin)
ABSTRACT Earthworms originating from Europe (e.g., Lumbricus spp., Aporrectodea spp.), which are common in the United States and southern Canada can create hazardous conditions at airports by attracting birds that pose a threat to aircraft. These nonnative earthworms are also considered pests on golf courses and sports fields, as well as having detrimental effects on temperate boreal forests. No toxicants or repellents are currently registered for earthworm control in the United States. Our purpose was to identify products that could be used to repel or suppress nonnative earthworms on airports or other managed sites where they pose a hazard or nuisance. We conducted experiments on the National Aeronautics and Space Administration's Plum Brook Station, Ohio, USA, and at an area about 15 km south of this site, during 2007–2013. We hypothesized that either abrasiveness or extreme low or high pH levels would be characteristic of an efficacious repellent. Ammonium sulfate fertilizer (an acidic treatment) repelled Lumbricus terrestris in choice tests. However, 6 applications of ammonium sulfate over 2 years only reduced the field density of Aporrectodea spp., and not Lumbricus spp. Application of tea‐seed cake pellets (TSP), a saponin‐rich byproduct of tea oil (Camellia oleifera) manufacture that causes earthworms to come to the surface and desiccate, temporarily reduced densities of both Lumbricus and Aporrectodea spp. in field plots. However, several applications per year would probably be needed for sustained control. Ring‐billed gulls (Larus delawarensis) showed no apparent adverse effects over a 48 hour period from feeding on TSP‐killed earthworms. We discuss potential value and limitations of TSP and other methods for managing earthworms to reduce airport bird‐strike hazards. © 2015 The Wildlife Society.